ANALISIS PERTANDINGAN OLIMPIADE OLAHRAGA SISWA NASIONAL CABANG KARATE TINGKAT SMA KOTA PONTIANAK - Nana, Prisila; G Simanjuntak, Victor; Haetami, Mimi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstrakThe purpose of this research is Â how to analyze the National Student Sports Olympic Games (O2SN) Karate Branch of the High School in Pontianak City.This study aims to determine the success of the attack to face the next match. The research method used is a survey technique taking with descriptive analysis research. The subject of this research 14 matches. analysis techniques were quantitative percentages. The results of the study showed that the success of the attack technique on O2SN karate branch in the high school level in Pontianak City was as follows: 1) the punch attack technique that gained kizame points 43.37% and the tsuki gyaku 28.57% and the blow attack technique that did not get kizame points 56.53% and gyaku tsuki 71.43%. Kick attack techniques that get maegeri points 0%, mawashi scores 12.12% and ushiro 15%. Kick attack techniques did not get maegeri points 100%, mawashi geri 187.88% and ushiro 85%. at the National Student Sports Olympic Games (O2SN) Karate Branch in the City of Pontianak high-level attack techniques were more effective against the acquisition of points in the kumite men's match, namely the kizame attack technique.Keywords: Â Match Analyze, Karate